Peran Kepala Sekolah Dalam Menanamkan Nilai-Nilai Keislaman Pada Siswa SD Muhammadiyah Program Unggulan Jatipuro - Ayuningtyas Noviani; Wahdan Najib Habiby (Jurnal Elementaria Edukasia, 2023)
This study aims to determine the role of school principals in instilling Islamic values in students of the superior program of Muhammadiyah Elementary School in Jatipuro. This research includes qualitative research using a case study design. This research was conducted at SD Muhammadiyah Program Unggulan Jatipuro, Jatipuro District, Karanganyar Regency. Data collection in this study was carried out using interviews, documentation, and observation methods. The stages of data analysis in this study are data reduction, data presentation, and conclusion drawing. The results of this study are Islamic values taught at SD Muhammadiyah Jatipuro Excellent Programme, namely the value of faith, the value of worship, and the value of morals. The role of the principal at SD Muhammadiyah Program Unggulan Jatipuro as an educator is that the principal also teaches students and provides good examples and role models for students and other school members. As a manager, the principal participates in making Islamic activity programs and requires teachers to attend Islamic studies at school. As a leader, the principal gives tasks to teams, especially teachers, to achieve the goals that have been made and their targets. As a motivator, the principal encourages all members of the school, especially teachers, to be enthusiastic about providing knowledge to students. As an administrator, the principal participates in managing religious activities and is assisted by members to make reports on embedding Islamic values to students, then reported to the principal. As a supervisor, the principal oversees the performance of the implementation team and monitors student behaviors. As an innovator, the principal requires teachers and teams to participate in religious activities, so that they can increase their knowledge and can be taught to students.